2008
DOI: 10.1093/pcp/pcn059
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of B-class complex proteins involved in tepal development in Phalaenopsis orchid

Abstract: In our previous studies, we identified four DEFICIENS (DEF)-like genes and one GLOBOSA (GLO)-like gene involved in floral organ development in Phalaenopsis equestris. Revealing the DNA binding properties and protein-protein interactions of these floral homeotic MADS-box protein complexes (PeMADS) in orchids is crucial for the elucidation of the unique orchid floral morphogenesis. In this study, the interactome of B-class PeMADS proteins was assayed by the yeast two-hybrid system (Y2H) and glutathione S-transfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 42 publications
2
34
0
Order By: Relevance
“…Genes in the B-class AP3, C/D-class and E-class clades are well known for their roles in the specification of floral organ identity and have been well studied in P. equestris. These expanded clades including members with differential expression patterns in orchid floral organs, as well as divergent encoded protein domains, support the unique evolutionary routes of these floral organ identity genes associated with the unique labellum and gynostemium innovation in orchids [47][48][49][50] . Notably, one of the three gene copies in the expanded AGL6 clade had an expression pattern similar to that of the AP3-like PeMADS4 gene, which is specifically expressed in the labellum 51 .…”
Section: Mads-box Gene Family Analysismentioning
confidence: 71%
“…Genes in the B-class AP3, C/D-class and E-class clades are well known for their roles in the specification of floral organ identity and have been well studied in P. equestris. These expanded clades including members with differential expression patterns in orchid floral organs, as well as divergent encoded protein domains, support the unique evolutionary routes of these floral organ identity genes associated with the unique labellum and gynostemium innovation in orchids [47][48][49][50] . Notably, one of the three gene copies in the expanded AGL6 clade had an expression pattern similar to that of the AP3-like PeMADS4 gene, which is specifically expressed in the labellum 51 .…”
Section: Mads-box Gene Family Analysismentioning
confidence: 71%
“…Both PI and AP3 in Tarenaya have diverged in expression levels. MADS box B-class gene homologs in the AP3 lineage as well as TCP members have been implicated in the establishment of monosymmetric flowers in monocots, including Orchidaceae species (Tsai et al, 2004(Tsai et al, , 2008Mondragón-Palomino and Theissen, 2009;Bartlett and Specht, 2010;Preston and Hileman, 2012), PI genes have contributed to floral diversification in Asterids (Viaene et al, 2009), and B-class genes have contributed to Aquilegia floral diversification (Kramer et al, 2007). Thus, it is possible that both B-class and TCP genes have an impact on floral monosymmetry in Cleomaceae.…”
Section: Discussionmentioning
confidence: 99%
“…The obligate B protein heterodimers in snapdragon and Arabidopsis are required both for organ identity specification and to maintain B gene expression in an autoregulatory circuit Tröbner et al, 1992;Zachgo et al, 1995;Davies et al, 1996;Hill et al, 1998;Tilly et al, 1998;Manchado-Rojo et al, 2012). In addition to heterodimers of AP3/PI-like proteins, homodimers of AP3 orthologs have been found in basal eudicots like columbine (Aquilegia vulgaris) and opium poppy (Papaver somniferum) (Drea et al, 2007;Kramer et al, 2007), whereas homodimer formation of PI orthologs has been demonstrated so far for petaloid monocots like the tulip (Tulipa gesneriana) and the orchid Phalaenopsis equestris (Kanno et al, 2003;Tsai et al, 2008). However, a function could not be assigned to homodimers formed by either AP3 or PI orthologs.…”
Section: Introductionmentioning
confidence: 99%